STORAGE AND COLLECTION RIVER DEBRIS PLANNING IN TANGGUL RIVER SURAKARTA CITY, INDONESIA AS SOURCE OF WASTE MANAGEMENT USING THE MULTI-CRITERIA DECISION-MAKING METHOD - Sari, Mega Mutiara; Inoue, Takanobu; Nafisah, Aninda Putri; Harryes, Regil Kentaurus; Yokota, Kuriko; Septiariva, Iva Yenis; Suhardono, Sapta; Kato, Shigeru; Notodarmojo, Suprihanto; Suryawan, I Wayan Koko (UI Scholars Hub, 2022)
The Tanggul River in Surakarta City is a tributary that empties into the Bengawan Solo River. Domestic activities located on river borders can pollute with the waste generation. Therefore, managing waste sources such as storage and collection is crucial in waste management. This study aims to analyze waste management from river debris storage and collection around the study site. The technique used in this research is direct observation of the study area and performing a decision analysis for alternative processing. Decision support system has one model, namely Multi-Criteria Decision Making for environmental development. The activities for collecting and sorting river debris in the Tanggul River are not yet available. The existing river debros collection used a 7 cm diameter net that has been installed at the sluice gate of the Tanggul River. Considering aspects or criteria in implementing accommodation activities needs to be carried out before determining the best alternative. Therefore, several measures need to be considered in determining the container based on SNI 19-2454-2002 concerning Operational Procedures for Urban Waste Management and Minister of Public Works Regulation Number 3 of 2013. The collection activity in alternative 1 uses the Brute Boom system: Heavy Duty Containment Boom equipped with a galvanized weir mesh net attached under the boom. The collection activity in alternative 2 uses a floating cube. The floating cube is a cube-shaped Waste holder that can float in the river to effectively hold waste floating on the surface of the river body. It is imperative to prevent river pollution from activities by providing infrastructure for storing and collecting waste. However, it does not have a more significant impact, such as the Tanggul River to the Bengawan Solo River in Surakarta City.